"Getting prices right", how important is it? a CGE modeling approach - Gaspay, Manuel S. (Philippine Review of Economics and Business (formerly The Philippine Review of Business and Economics), 1993)
A dynamic computable general equilibrium (CGE) model of the Philippines, with alternative versions of fiscal policy behavior, is constructed to examine the neo-classical claim about the relationship between trade restrictions and economic performance. The results indicate that the economic output and income distribution influences of price distortion from tariffs are indeed modest. In the growth process, it is the government revenue role of tariffs that matter rather than the impact of tariffs on factor allocation efficiency. There must be consistency, therefore, between the government's fiscal policy and its trade liberalization program for the latter to be successfully implemented.